2008
DOI: 10.1037/0096-1523.34.5.1305
|View full text |Cite
|
Sign up to set email alerts
|

Category and perceptual interference in second-language phoneme learning: An examination of English /w/-/v/ learning by Sinhala, German, and Dutch speakers.

Abstract: The present study investigated the perception and production of English /w/ and /v/ by native speakers of Sinhala, German, and Dutch, with the aim of examining how their native language phonetic processing affected the acquisition of these phonemes. Subjects performed a battery of tests that assessed their identification accuracy for natural recordings, their degree of spoken accent, their relative use of place and manner cues, the assimilation of these phonemes into native-language categories, and their perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 49 publications
7
32
0
Order By: Relevance
“…For example, infants develop L1 phonetic specializations prior to when they are thought to learn words (e.g., Kuhl et al, 1992;Werker and Tees, 1984a), cross-language neuroimaging differences in adults have been found to occur prior to lexical processing (e.g., Näätänen et al, 1997;Raizada et al, 2010), and speakers of tone languages can have auditory processing advantages for nonspeech pitch contours that are analogous to the tone contrasts in their language (e.g., Krishnan and Gandour, 2009). Based on this kind of evidence, our hypothesis has been that there is speech-specific specialization of auditory or phonetic processing that occurs independently from linguistic categorization (Iverson et al, , 2008. This auditory/phonetic specialization may be adaptive for L1 categorization (e.g., Kuhl et al, 2008), but interfere with L2 learning and categorization when it makes the critical L2 phonetic differences less salient (Iverson et al, , 2008.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…For example, infants develop L1 phonetic specializations prior to when they are thought to learn words (e.g., Kuhl et al, 1992;Werker and Tees, 1984a), cross-language neuroimaging differences in adults have been found to occur prior to lexical processing (e.g., Näätänen et al, 1997;Raizada et al, 2010), and speakers of tone languages can have auditory processing advantages for nonspeech pitch contours that are analogous to the tone contrasts in their language (e.g., Krishnan and Gandour, 2009). Based on this kind of evidence, our hypothesis has been that there is speech-specific specialization of auditory or phonetic processing that occurs independently from linguistic categorization (Iverson et al, , 2008. This auditory/phonetic specialization may be adaptive for L1 categorization (e.g., Kuhl et al, 2008), but interfere with L2 learning and categorization when it makes the critical L2 phonetic differences less salient (Iverson et al, , 2008.…”
Section: Introductionmentioning
confidence: 97%
“…Based on this kind of evidence, our hypothesis has been that there is speech-specific specialization of auditory or phonetic processing that occurs independently from linguistic categorization (Iverson et al, , 2008. This auditory/phonetic specialization may be adaptive for L1 categorization (e.g., Kuhl et al, 2008), but interfere with L2 learning and categorization when it makes the critical L2 phonetic differences less salient (Iverson et al, , 2008.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Listeners were clearly sensitive to distinctions that were not necessarily reflected in their categorization patterns. Iverson et al ͑2008͒ suggested that distortions in perceptual space also contribute to L2 learning.…”
Section: Limitationsmentioning
confidence: 99%